Revisitation: A Transgender Phenomenology of the Media Image - Keegan, Cáel M. (MedieKultur: Journal of Media and Communication Research, 2016)
How might certain moving images move us into transgender becoming? Th e recent proliferation of transgender images in the media of the Global North has been widely regarded as supporting transgender political and social equality.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Crossdressing Cinema: An Analysis of Transgender Representation in Film - Miller, Jeremy Russell (2012)
Transgender representations generally distance the transgender characters from the audience as objects of ridicule, fear, and sympathy. This distancing is accomplished through the use of specific narrative conventions and visual codes. In this dissertation, I analyze representations of transgender individuals in popular film comedies, thrillers, and independent dramas. Through a textual analysis of 24 films, I argue that the narrative conventions and visual codes of the films work to prevent identification or connection between the transgender characters and the audience. The purpose of this distancing is to privilege the heteronormative identities of the characters over their transgender identities. This dissertation is grounded in a cultural studies approach to representation as constitutive and constraining and a positional approach to gender that views gender identity as a position taken in a specific social context. Contributions are made to the fields of communication, film studies, and gender studies through the methodological approach to textual analysis of categories of films over individual case studies and the idea that individuals can be positioned in identities they do not actively claim for themselves. This dissertation also makes a significant contribution to conceptions of the gaze through the development of three transgender gazes that focus on the ways the characters are visually constructed rather than the viewpoints taken by audience members. In the end, transgender representations work to support heteronormativity by constructing the transgender characters in specific ways to prevent audience members from developing deeper connections with them.
Accepted: 2012-10-19T15:30:33Z
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Gendering the Nation Canadian Women's Cinema - Armatage, Kay; Banning, Kass; Longfellow, Brenda (University of Toronto Press, 2016)
Since Nell Shipman wrote and starred in Back to God's Country (1919), Canadian women have been making films. The accolades given to film-makers such as Patricia Rozema (I've Heard the Mermaids Singing, When Night is Falling), Alanis Obomsawin (My Name Is Kahenttiiosta, Walker), and Micheline Lanctot (Deux Actrices) at festivals throughout the world in recent years attest to the growing international recognition for films made by Canadian women. With Gendering the Nation the editors have produced a definitive collection of essays, both original and previously published, that address the impact and influence of a century of women's film-making in Canada. In dialogue with new paradigms for understanding the relationship of cinema with nation and gender, Gendering the Nation seeks to situate women's cinema through the complex optic of national culture. This collection of critical essays employs a variety of frameworks to analyse cinematic practices that range from narrative to documentary to the avant garde.
OCLC: 944178123
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Créatrice; _Nettoyé

Alanis Obomsawin the Vision of a Native Filmmaker - Lewis, Randolph (University of Nebraska Press, 2006)
In more than twenty powerful films, Abenaki filmmaker Alanis Obomsawin has waged a brilliant battle against the ignorance and stereotypes that Native Americans have long endured in cinema and television.
OCLC: 1200868429
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Épistémologies autochtones; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

Decolonizing the Lens of Power: Indigenous Films in North America - Kerstin, Knopf (Rodopi, 2008)
Knopf samples a variety of Native American filmmaking genres, including documentary, short films, and full-length narrative films, providing a detailed synopsis and content analysis of several films. Since its genesis in the early 19005, film has been an effective colonizing tool, impacting Indigenous peoples around the globe.
Issue: 4 Pages: 611-614
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Épistémologies autochtones; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

New Black Queer Cinema - Wallenberg, Louise (New Queer Cinema: A Critical Reader, 2004)
In 1989, three years before the New Queer Wave was even invented or discovered, two very different yet interconnected films were produced on either side of the Atlantic. Both soon became critically successful and both would win a number of prizes at different international film festivals and venues. In retrospect, these two films have come to constitute the very incitement to the Wave. British filmmaker Isaac Julien’s Looking for Langston premiered in early 1989 and American filmmaker Marlon Riggs’s Tongues Untied premiered later that same year, the latter including a still photo from the former so as to pay homage
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Our Stories Have Never Been Told: Preliminary Thoughts on Black Lesbian Cultural Production as Historiography in The Watermelon Woman - Richardson, Matt (Black Camera, 2011)
Cheryl Dunye's 1996 film The Watermelon Woman earned a place in cinematic history as the first feature-length narrative film written and directed by an out black lesbian about black lesbians. This article examines how the film provides an important opportunity to mark the burgeoning genre of black queer documentary as a historiographical medium. The documentary film is a tool that highlights underexplored issues in black experience and provides a cultural site for imagining new possibilities for black lesbian subjectivity and creating innovative approaches to representing sexuality in black filmmaking.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Struggles for Representation: African American Documentary Film and Video - Reid, Mark A. (American Literature, 2000)
Struggles for Representation examines over 300 non-fiction films by more than 150 African American film/videomakers and includes an extensive filmography, bibliography, and excerpts from interviews with film/videomakers. In eleven original essays, contributors explore the extraordinary scope of these aesthetic and social documents and chart a previously undiscovered territory: documentaries that examine the aesthetic, economic, historical, political, and social forces that shape the lives of black Americans, as seen from their perspectives.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

From a Real Place and Real People: Interview with Mississippi Damned Writer/Director Tina Mabry - Moore, Marlon Rachquel (Black Camera, 2011)
Marlon Rachquel Moore interviews emerging independent filmmaker Tina Mabry about her southern upbringing, racial and sexual consciousness, and the joys and turbulence of bringing her first feature-length film, Mississippi Damned, to the silver screen. Mississippi Damned is based on Mabry's family and set in her hometown of Tupelo, Mississippi.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice noir.e; _Nettoyé

The Witch’s Flight: The Cinematic, the Black Femme, and the Image of Common Sense - Keeling, Kara (Duke University Press, 2007)
Kara Keeling contends that cinema and cinematic processes had a profound significance for twentieth-century anticapitalist Black Liberation movements based in the United States. Drawing on Gilles Deleuze’s notion of “the cinematic”—not just as a phenomenon confined to moving-image media such as film and television but as a set of processes involved in the production and reproduction of social reality itself —Keeling describes how the cinematic structures racism, homophobia, and misogyny, and, in the process, denies viewers access to certain images and ways of knowing. She theorizes the black femme as a figure who, even when not explicitly represented within hegemonic cinematic formulations of raced and gendered subjectivities, nonetheless haunts those representations, threatening to disrupt them by making alternative social arrangements visible.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Lesbian "Making-of" Documentaries and the Production of Lesbian Sex - Hankin, Kelly (The Velvet Light Trap, 2004)
The Velvet Light Trap 53 (2004) 26-39 On December 2, 2001, HBO began airing Project Greenlight, a twelve-part documentary series chronicling the production of a feature film by novice writer-director Pete Jones. With its spectacle of backroom dealings, unchecked egos, and human frailties, the television series capitalized on the contemporaneous success of like-minded "reality" programs such as Survivor and Temptation Island. Perhaps more closely, Project Greenlight also tapped into the current vogue for the "behind-the-scenes" and the "making-of" genres, represented by straight-to-video titles such as Star Trek-Deep Space Nine: Behind the Scenes (1993), Making of Jurassic Park (1995), and The Matrix Revisited (2001), television programs such as the Sundance Channel's Anatomy of a Scene, HBO's First Look, and MTV's Making the Video, and the proliferation of behind-the-scenes and making-of packaging on DVDs. A reflection of the growth of film-related ancillary products in the 1980s, the ever-expanding Hollywood ego, and the demands of a twenty-four-hour television cable market, the increased appearance of the making-of documentary format no doubt also reflects the renewed interest in amateur filmmaking promulgated by the age of desktop video. Perhaps as a manifestation of this interest, making-of documentaries have become increasingly more detailed in their coverage. Whereas the 1981 television special The Making of "Raiders of the Lost Ark" (Phillip Schuman) focuses mostly on the film's stunt work, special effects, location shoots, and set design, the recently released making-of documentary The Matrix Revisited focuses on script development, preproduction, production, postproduction, and exhibition, introducing viewers to costume designers, storyboard artists, and editors along the way. This attention to production detail can also be seen in Sundance's Anatomy of a Scene, which hones in on the construction, from music to costume to camera work, of a single scene. And certainly raising the bar on the level of detail included in the making-of genre is Project Greenlight, which is a "warts-and-all" look at film production, from squabbles over budgets to catering fiascos. Despite the making-of video's increased attention to the minutiae of filmmaking, one of the areas that remains outside the purview of most Hollywood making-of documentaries is the production of sex. Discussions about the cinematic logistics of creating a sex scene—how, when, and with what resources—are usually not featured in making-of documentaries. Of course, given our celebrity-driven culture, the question of sex vis-à-vis film production, particularly a Hollywood film production, is hardly absent from the publicity that surrounds a film. It is not uncommon to hear actresses or actors discussing what it was like to kiss another actor on the set. But these kinds of concerns are usually the province of entertainment magazines and television, not the province of ancillary related products such as the making-of video. While stories of roles requiring nudity or sex scenes abound on television shows such as Access Hollywood, Entertainment Tonight, and E! News Daily,these kinds of topics are less likely to appear in production-generated documentaries. Indeed, while the production of the provocative sex scene between Halle Berry and Billy Bob Thornton in Monster's Ball (Marc Forster, 2001) generated much discussion on television entertainment programs, talk shows, and newsmagazines, it was the film's prison execution sequence that was featured in the Sundance Channel's making-of special on the film. Given the lack of focus on sex scenes in most making-of documentaries, it is interesting to note that the two existing making-of documentaries for lesbian-made, lesbian-themed feature films—The Making of Bar Girls (1995) and Moments: The Making of Claire of the Moon (1992)—both heavily focus on the production of lesbian sex. Moreover, both lesbian making-of documentaries emphasize the cast's and the crew's sexual titillation over the creation of sexual sequences. In this essay I look at what this strategy reveals about the collective climate and concerns of lesbian feature filmmaking in the United States today.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Petit guide sur le cinéma des femmes - Ouellet-Cummings, Catherine (Ciné-Bulles, 2011)
Thérèse Lamartine est bien connue des milieux féministes. Détentrice d’une maîtrise en études cinématographiques, elle a publié Elles, cinéastes... ad lib, en 1985, aux Éditions Remue-ménage, dans lequel elle présentait des réalisatrices de diverses origines, actives entre 1895 et 1981. En 2009, elle publiait Soudoyer Dieu, un roman scrutant la longue et inconsolable douleur d’un groupe de femmes après la tuerie de Polytechnique. Avec Le Féminin au cinéma, une petite plaquette consacrée aux films «de femmes» ou, comme elle le précise, aux films qui «sculptent un art du mieux-vivre la mixité dans nos sociétés ou [qui] débrident les stéréotypes et nous dérident à la fois», Lamartine ouvre les portes d’un monde cinématographique souvent méconnu et rend hommage à des femmes de cinéma, autant derrière que devant la caméra. En sortant ces femmes de l’ombre, elle met au jour un cinéma riche et original, mais méconnu.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créatrice; _Nettoyé

"Just Because I'm a Lesbian Doesn't Mean I'm Evolved" The "Bad Queer" Women's Comedic Web Series - San Filippo, Maria (Velvet Light Trap, 2020)
The queer women's comedic web series that have flourished in the last decade, serving as launching pads for their creators, coincided with media-industry nichification's segmentation of a consumer population regarded by advertisers and content providers as one monolithic LGBTQ community. The series I examine-from The Slope, which premiered in 2010, to Strangers, released in 2017-voice their creators' and characters' marginalization from and even opposition to such an imagined community, through recourse to what I call a "bad queer" rhetorical practice, which uses ironic metacommentary to critique assimilationist values and tropes alongside queer identity policing. These series emerged, at least initially, as an alternative sphere of queer media production and a queer discursive mode that employs disidentification as a politicized strategy to challenge dominant LGBTQ scripts. Offering an irreverent alternative to mainstream and millennial LGBTQ cultural products, these "bad queer" web series express the plurality of the queer "community" and expose political contestations within its ranks, and in so doing serve as brand differentiation for a new generation of queer media producers.
Num Pages: 65-77 Place: Austin, United States
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé

Uplift Cinema: The Emergence of African American Film and the Possibility of Black Modernity - Field, Allyson Nadia (Duke University Press, 2015)
Allyson Nadia Field recovers the forgotten body of African American filmmaking from the 1910s which she calls uplift cinema. These films were part of the racial uplift project, which emphasized education, respectability, and self-sufficiency, and weren't only responses to racist representations of African Americans in other films.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice noir.e; _Nettoyé

"Rock-a-Bye, Baby!": Black Women Disrupting Gangs and Constructing Hip-Hop Gangsta Films - Smith-Shomade, Beretta E. (Cinema Journal, 2003)
This essay examines the cultural specificity of the gangster genre. In hip-hop gangsta films, the inclusion of black women as central to the gangster business not only transforms the gangster genre but, more important, adheres to black cultural norms. The films New Jack City, Sugar Hill, and Set It Off serve as case studies.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

On How Queer Cinema Might Feel. - Quinlivan, Davina (Music, Sound, and the Moving Image, 2015)
Examines the soundscapes of Derek Jarman's film "Blue" (1993) and Isaac Julien's video installation 'True north' (2007), and the way they contribute to promoting embodied responses in the viewer. Draws on the writings of Luce Irigaray and Laura U. Marks to explore the relationship between haptic theory and queer spectatorship.
Num Pages: 63-77
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Paris is burning: Intersectionality in 90s Queer Cinema. - Brew, Tara (Film Matters, 2019)
The overlap of marginalised race and sexuality is highlighted in the 1990 documentary "Paris is burning" which depicts the life of New York's black and Latino drag queens. The author offers an analysis of the social circumstances that gave birth to this culture which originated in 1980s Harlem.
Num Pages: 7-18
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Ciné-parcours dans l'Europe contemporaine : routes nécessaires, routes symboliques - Gandolfi, Paola (Cinémas : Revue d'études cinématographiques = Journal of Film Studies, 2010)
Cette vidéaste regarde - et nous fait regarder - la frontière comme un espace mental et matériel : les interviews, la voix over dont le texte apparaît à l'écran, les citations de textes, les images, les sons et le found footage sont combinés de façon à donner un aperçu saisissant et intime à la fois des conditions de vie des femmes (division du travail, prostitution, violence à l'égard des femmes dans les rues, etc.) propres aux régions frontalières, c'est-à-dire se définissant en fonction des contraintes liées à leur position limitrophe, mais offrant une certaine liberté aux gens qui y vivent du fait, justement, de cette position. Il est intéressant de voir comment le road movie permet de réaffirmer la place de l'automobile comme pur moyen de mobilité, mais en même temps comment il nous oblige à nous concentrer sur un autre type de mobilité, que Walter Moser (2008, p. 9) appelle la « médiamotion », soit : une forme de mobilité que nous procurent les médias mais qui, dans un certain sens, remplace ou redouble le déplacement physique en offrant aux êtres humains une expérience presque paradoxale : le contact à distance. On peut également voir dans le road movie contemporain un « road movie interculturel6», parce que la route y trace «un espace imaginaire particulièrement apte à figurer la complexité et les asymétries de l'interculturel » (Gin 2008, p. 41), mais également parce que : l'intetculturalité [...] du road movie résiderait en ce sens dans le mouvement que subit un principe ou une pulsion d'identification culturelle ne pouvant ni se réaliser ou s'assouvir - narrativement, visuellement - dans l'univocité d'un arrêt sur image, ni pour autant s'épuiser on the road Xp. 44). En fait, la mobilité transnationale se situant au centre de cette production filmique «accentuée» donne lieu à un ensemble de tentatives en constante évolution, où les identités culturelles en devenir peuvent être «constamment reformulées dans une perspective future, bien que conditionnées par des liens historiques et des devoirs avec le passé» (Grillo, Riccio et Salih 2000, p. 16), aussi bien que par les liens qu'entretiennent les migrants et les exilés avec leur identité et leur culture d'origine.
Num Pages: 23 Place: Montréal
Keywords: 1-Cinéma; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Straight Skin, Gay Masks and Pretending to Be Gay on Screen - Padva, Gilad (Routledge, 2020)
Straight Skin, Gay Masks and Pretending to Be Gay on Screen examines cinematic depictions of pretending-to-be-gay, assessing performances that not only reflect heteronormative and explicitly homophobic attitudes, but also offer depictions of gay selfhood with more nuanced multidirectional identifications. The case of straight protagonists pretending to be gay on screen is the ideal context in which to study unanticipated progressivity and dissidence in regard to cultural construction of human sexualities in the face of theatricalized epistemological collapse. Teasing apart the dynamics of depictions of both sexual stability and fluidity in cinematic images of men pretending to be gay offers new insights into such salient issues as sexual vulnerability and dynamics and long-term queer visibility in a politically complicated mass culture which is mostly produced in a heteronormative and even hostile cultural environment. Additionally, this book initially examines queer uses of sexuality masquerade in Alternate Gay World Cinema that allegorically features a world pretending to be gay, in which straights are harassed and persecuted, in order to expose the tragic consequences of sexual intolerance. Films and TV series examined as part of the analysis include The Gay Deceivers, Victor/Victoria, Happy Texas, William Friedkin’s Cruising and many other straight and gay screens. This is a fascinating and important study relevant to students and researchers in Film Studies, Media Studies, Gender Studies, Queer Studies, Sexuality Studies, Communication Studies and Cultural Studies.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Coquie Hughes: Urban Lesbian Filmmaker Introduction to Yvonne Welbon’s Interview with Coquie Hughes - Brody, Jennifer Devere (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Toni Morrison purportedly began her career as a novelist because she noticed a dearth of books about black women. As a result of this limitation, Morrison desired to write books “for people like [her], which is to say black people, curious people, demanding people—people who can’t be faked, people who don’t need to be patronized.”¹ Similarly the writer, director, and filmmaker Coquie Hughes (born Latasha Iva Hughes in Chicago in 1970) has produced narratives that feature an array of queer black women—“Girls Like Us” as she calls them in her web series—who are curious, demanding, flawed, and
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

The Circuitous Route of Presenting Black Butch: The Travels of Dee Rees’s Pariah - Declue, Jennifer (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
At the 2012 Golden Globe awards, during her acceptance speech for the Best Actress award for her performance in The Iron Lady (Phyllida Lloyd, 2012), Meryl Streep gave a shout-out to Adepero Oduye for her role as Alike in Dee Rees’s feature film Pariah (2011). The sentiment behind this esteemed acknowledgment was that brilliant performances in important independent films were overlooked and deserved recognition. Streep would go on to win the Best Actress Oscar for a her portrayal of Britain’s first woman prime minister, the a ultraconservative Margaret Thatcher.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

A Cosmic Demonstration of Shari Frilot’s Curatorial Practice - Rastegar, Roya (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Shari Frilot is a filmmaker and curator whose creative practice has been driven by sustained explorations of sexuality, technology, desire, cosmic and subatomic structures, mixed-raced identity, and chaos. She has often expressed her modus operandi in the following terms: “It’s impossible to see a cloud when you’re in the middle of it. You have to move outside of the cloud to really get a sense of it.” By continually shifting between the outside and inside of a given framework—whether institutional or personal—Frilot has developed keen modes of challenging conventional structures for understanding and engaging the moving image.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Stepping Out on Faith: Interview with Coquie Hughes - Welbon, Yvonne (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
I grew up on the West Side of Chicago, where it was infested with gangs and drugs and violence. But I was always the type of person that wanted to be better than my environment, and I was also the type of person that didn’t want people to underestimate me because of where I came from. And so I made up in my mind, even as a young child, that I wanted to be somebody. I love making movies. I’ve wanted to be who I am ever since I saw Sidney Lumet’s movie The Wiz (1978).
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Birth of a Notion: Toward Black, Gay, and Lesbian Imagery in Film and Video - Parkerson, Michelle (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In mainstream media, gays and lesbians of color are either woefully present or predictably absent. The litany of black gay and lesbian characters in Hollywood films and network television reads like its own form of blackface. They range from the burly, black “bulldagger” as whore house madam in the 1933 film The Emperor Jones (starring Paul Robeson) to the predatory lesbian vamp in Spike Lee’s 1983 She’s Gotta Have It ; from Eddie Murphy’s ultracamp Miss Thing hairdresser on NBC’s Saturday Night Live to the snap! queen duo on Fox TV’s In Living Color. These relentless stereo types are part of
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

“Invite Me In!”: Angela Robinson at Hollywood’s Threshold - White, Patricia (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In 2005 Angela Robinson released her spy spoof, D.E.B.S. (2004). Robinson first realized the project as the short film D.E.B.S. (2003) through a training program with POWER UP (Professional Organization of Women in Entertainment Reaching Up), the only 501(c)(3) nonprofit film production company and educational organization for women and the GLBTQ community. In 2005 she also became the second black woman and first black lesbian to direct a studio feature, the Disney film Herbie Fully Loaded starring Lindsay Lohan. This moment marked the beginning of the black lesbian media maker hyphenate as Angela Robinson moved to television and began working on The L Word as a writer, director, and eventually producer. Patricia White's essay in this section, "'Invite Me In!': Angela Robinson at the Hollywood Threshold," offers an in-depth exploration of her career trajectory.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Stereotypy, Mammy, and Recovery in Cheryl Dunye’s The Watermelon Woman - Wimbley, Karin D. (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
The Mammy has been in our field of vision as a popular icon representing black womanhood for more than a century in literature, film, and television and in consumer and material culture.¹ Described as an asexual, rotund slave of older age whose sole responsibility is to take care of her master’s children, Mammy is a beloved character who represents all that is nurturing and maternal. She is dark-skinned and boisterous and thought to have mannish features such as large feet and hands. Mammy wears a large skirt, hiding her sex, and covers her nappy hair with a bandanna or handkerchief.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Hollywood at the Intersection of Race and Identity - Konzett, Delia Caparoso. (Rutgers University Press, 2020)
Hollywood at the Intersection of Race and Identity explores the ways Hollywood represents race, gender, class, and nationality at the intersection of aesthetics and ideology and its productive tensions. This collection of essays asks to what degree can a close critical analysis of films, that is, reading them against their own ideological grain, reveal contradictions and tensions in Hollywood’s task of erecting normative cultural standards? How do some films perhaps knowingly undermine their inherent ideology by opening a field of conflicting and competing intersecting identities? The challenge set out in this volume is to revisit well-known films in search for a narrative not exclusively constituted by the Hollywood formula and to answer the questions: What lies beyond the frame? What elements contradict a film’s sustained illusion of a normative world? Where do films betray their own ideology and most importantly what intersectional spaces of identity do they reveal or conceal?
Pages: ix, 357 pages :
Keywords: 1-Cinéma; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Filming Power and the Powerless: Zhao Liang’s Crime and Punishment (2007) and Petition (2009) - Li, Jie (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
This article discusses two recent works by emerging documentary auteur Zhao Liang, Crime and Punishment(2007) and Petition(2009). These penetrating observations of state-society relations in contemporary China render visible those who are un(der)represented, critique the deception of mass media images, and show the various complex ways in which power is connected to surveillance and visibility. Thus the filmmaker, his camera, and the spectators are implicated in power relationships as we cast voyeuristic, panoptic, activist, empathetic, or critical gazes upon the representatives of state power and upon the disenfranchised.
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Marking the Body: The Axiographics of the Visible Hidden Camera - Nornes, Abé Mark (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
This chapter contemplates the ethical dimensions of the specific brand of observational cinema found in China. Because there is no popular understanding of independent documentary—and also because filmmakers almost invariably use amateur video cameras and shoot alone—many subjects are oblivious to the fact that their images are being captured for films being screened around the world. It is in this sense that, while their cameras are perfectly visible, they are also hidden. This enables directors to capture “life unawares,” as if people were being shot by a hidden camera. In this context, directors make the films they want, ignoring the ethical implications of shooting people without being upfront about their intentions or asking for consent. The chapter closely examines a set of films to explore the axiographics of the documentary, in other words how ethics is rendered in the time and space of the moving image.
Keywords: 1-Cinéma; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

“To Whom Do Our Bodies Belong?”: Being Queer in Chinese DV Documentary - Robinson, Luke (DV-made China : digital subjects and social transformations after independent film, 2015)
In 1990s post-Reform China, a growing number of people armed with video cameras poured out upon the Chinese landscape to both observe and contribute to the social changes then underway. This digital turn has given us a 'DV China' that includes film and media communities across different social strata and disenfranchised groups. This study takes stock of these phenomena by surveying the social and cultural landscape of grassroots and alternative cinema practices.
Keywords: 1-Cinéma; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

DV and the Animateur Cinema in China - Voci, Paola (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
Film scholarship on the movie-making, movie-viewing, and movie-circulating practices that have developed since the mid-1990s in China has appropriately emphasized the role played by the rise of digital video (DV) and its impact on independent and, in particular, documentary filmmaking. In this chapter, I want to explore one line of development in DV independent production that has received much less attention—what I call animateur cinema—which concerns short digital animations that are made by and/or circulated for online (or on-mobile) moviemakers/viewers. Fan-originated digital animation or egao animation can also be found online, but my focus is on animateur cinema
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Crossing Cameras in China: Christian Aesthetics and Realized Fictions - Zito, Angela (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
The films of director Gan Xiao’er are the first narrative features to take up Chinese Christians in their everyday concerns. This chapter discusses a pair of his films, one a fiction feature, the other a documentary made about taking that feature on the road and showing it in churches. It is about filmmaking practice—and especially documentary—as social occasion, as the concatenation between people of self-reflective moments of cultural creativity and critique. By social occasion, I mean that Gan has documented in the second film the moments of self-conscious “participation” in the fiction feature and in the documentary itself.
Keywords: 1-Cinéma; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Rephrasing the Feitiço: A New Episteme for Perverse Characters - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
Interesting and challenging Hollywood-style films that centre on sexually transgressive characters are not easy to script. Many writers fail as a result of an over-valuation of image at the expense of psychologically complex and challenging subjectivity. A hook for exploring the nature of this phenomenon lies in the notion of ‘involving and disturbing’, with a focus on how films might represent it and how audiences might perceive it, and with attention paid to how characters might be constructed. The chapter expands on how this notion of audience engagement might engage with screenwriting as a design function, aimed to construct characters in visual terms yet through words rather than pictures. In addressing certain epistemic limitations to writing character complexity, an alternative epistemic framing for ‘perverse’ characters is considered in terms of characterological ‘is-ness’, philosophical constitution and behaviours and actions.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Cinema's Queer Witness: Ira Sachs's Last Address and the Indifferent View - Rodness, Roshaya (CR: The New Centennial Review, 2019)
Roshaya Rodness is a senior doctoral candidate in the Department of English and Cultural Studies at McMaster University. Her dissertation addresses recent movements in queer theory with a special focus on cinema, poststructuralist ethics, and the nonhuman. She has published in Canadian Literature, Chiasma: A Site for Thought , and World Picture on topics that include contemporary film, indigenous authorship, postcontinental philosophy, and dream theories.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; _Nettoyé

All About Almodóvar’s Men - Rey, Juan; Uceda Pérez, Francisco (Peter Lang Inc., International Academic Publishers, 2017)
Pedro Almodóvar is an internationally acclaimed Spanish director. The national and international fascination over Almodóvar's cinema lies in his ability to reflect the problems of contemporary society, his lucidity in combining the urban and the rural, his ability to express the frustrations of modern man, as well as his freshness and spontaneity. Although the vast majority of studies on this Spanish director have focused on women and the gay world, his films are crowded with many types and archetypes of heterosexual men. This groundbreaking edited volume studies the men in the cinema of Almodóvar from a broad yet comprehensive and complementary perspective. Each chapter of All About Almodóvar's Men methodically dissects these male characters—their misery and their greatness, their frustrations and their desires—offering a kaleidoscopic view of man that goes beyond the narrow framework in which many studies have locked the rich cinema of Almodóvar.
Issue: vol. 8
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Identités diasporiques; _Nettoyé

Documenting What? Auto-Theory and Migratory Aesthetics - Bal, Mieke (A Companion to Contemporary Documentary Film, 2015)
As a method of learning more about contemporary culture than written documentation in libraries can provide, some 10 years ago I began to make documentary films. These films and what they showed me became, afterwards, secondary objects of analysis. Learning from and theorizing what I learned by reconsidering my own films yielded insights brought forth by the people “in” them. This became an ongoing, spiraling form of analysis-theory dialectic, and since my own films are the subject of my examination, I call it auto-theory. The best example is my video installation Nothing Is Missing (2006–2010). Here, 17 mothers of migrants, all living in different countries, explain in their own language what happened to their lives when one or more of their children decided to leave. These videos document a relationship, but not the one between maker and subject. The maker, here, is rather a facilitator, and the relationship that is documented, the one between the mother and someone close to her that has been modified by the migration of a child, is transformed in the process. The videos document this transformation itself, in the performance of it. This performative transformation is the subject of my article – it is what is being documented in the films.
Section: 6 _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/9781118884584.ch6
Keywords: 1-Cinéma; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé